Identifikasi Jamur Pada Pakaian Bekas Yang Dijual Di Pasar Toddopuli Kota Makassar - Ditaellyana Artha (Prodi D-III Analis Kesehatan niversitas Indonesia Timur, 2016)
Fungi are unicellular or multicellular organisms, which do not have chlorophyll so heterotrophic. Mushrooms can be easily grown in a moist, mold will grow more fertile again if cleanliness less intact. This situation often occurs in a collection of clothes used clothing imports are sold in the market. Wear old clothes or clothes that had been used by others, is very vulnerable to contracting skin diseases, particularly skin diseases caused by fungi. This study aims to identify the type of fungus anything contained in used clothing sold in markets Toddopuli Makassar, this kind of research is observational laboratory that is descriptive with a sample size of 10 (ten), a sampling technique that accidental sampling, the study was conducted in GG clinical laboratories. The results showed that of the 10 swab (swab) of used clothing sold in the market Toddopuli Makassar, found mildew on all the used clothing 100% with Aspergillus niger as much as 7 samples (70% ) and Aspergillus fumigatus as much as 3 samples (30%). The conclusion of this study is all samples are found fungi. To consumers to be cautious in buying and wearing second-hand clothes are bought and sold everywhere.